Assessment of Nitrate Leaching Risk in Hazelnut Areas of the Eastern Black Sea Region - Dengiz, Orhan (Asian Journal of Chemistry, 2010)
Prediction of nitrate leaching from cropland is crucial for preventing the surface or groundwater degradation and the economical balance. Nitrate leaching index model used in this study evaluates both soil hydrological groups requiring some soil characteristics and climatologically data. This study was carried out to evaluate and predict potential nitrate leaching risk from hazelnut fields in Ünye-Tekkiraz district of the eastern Black sea region of Turkey. The results show that while more than half of the study area (54.1 %) has high and very high risk category, 45.9 % of it has moderate level. Low nitrateleaching risk land was not found in the study area. In addition, many models include only quantitative estimates on the relationship between nitrate leaching and the environmental or management factors at the plot scale and do not allow to make evaluation for the regional or larger areas. Therefore, the main objectives of this study are (i) to determine seasonal trends of the potential nitrate leaching, (ii) to assess nitrate leaching risk and (iii) to classify the hazelnut areas associated with leaching risk and prepare risk map in Tekkiraz district of Ordu, Turkey.